2011
DOI: 10.2139/ssrn.1806888
|View full text |Cite
|
Sign up to set email alerts
|

Wage Structure Effects of International Trade: Evidence from a Small Open Economy

Abstract: In the last decades, international trade has increased between industrialised countries and between high-and low-wage countries. This important change has raised questions on how international trade affects the labour market. In this spirit, this paper aims to investigate the impact of international trade on wage dispersion in a small open economy. It is one of the few to: i) use detailed matched employer-employee data to compute industry wage premia and disaggregated industry level panel data to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 215 publications
0
4
0
Order By: Relevance
“…Lundin and Yun (2009) stated that exporting industries increase their profits. The firms earning higher profits pay higher wages (Caju, et al, 2011). Riker (2010) considered 60,000 manufacturing worker earnings for the period from 2006 to 2008, and found that exporting capability increases wage premium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lundin and Yun (2009) stated that exporting industries increase their profits. The firms earning higher profits pay higher wages (Caju, et al, 2011). Riker (2010) considered 60,000 manufacturing worker earnings for the period from 2006 to 2008, and found that exporting capability increases wage premium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The microdata group pursues three directions of research one of which is on wage differentials and modelling of earnings. The SES data is one of the main data sources for this group, used by many authors (see, e.g., Caju et al 2010Caju et al , 2009aMessina et al 2010;Dybczak and Galuscak 2010;Simón 2010;Pointner and Stiglbauer 2010).…”
Section: Access To Ses Microdata and European Projectsmentioning
confidence: 99%
“…Research studies are usually focused on examining the determinants of disparities in earnings. Earnings comparisons between different industries or regions are frequently performed (see, e.g., Stephan and Gerlach 2005;Caju et al 2010Caju et al , 2009b Bowles et al (2001). The overview of the analyses performed using SES data highlighted that, generally, the log hourly earnings are modelled.…”
Section: Research Potential Of Ses Microdatamentioning
confidence: 99%
See 1 more Smart Citation